Can someone please help me
The functions of F and G are defined as follows
f(x)=-3x^2-2 and g(x)=-4x-3
find f(3) and g(2)
simplify the answer as much as possible

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

so I know I do
F(x) = -3x^2-2
F(3)=-3(3)^2-2(3)
but im stuck after that what do i do now

from there you simplify using order of operations. exponents → multiplication → subtraction

where'd the second 3 come from in f(3)?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.